Analisis Efisiensi Biaya Produksi Sosis Dengan Menggunakan Informasi Akuntansi Diferensial Dalam Pengambilan Keputusan(Studi Kasus Pada PT. Ciomas Adisatwa Medan) - Bangun, Endayani Br; Arif, Muhammad; Wahyuni, Arnida (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2023)
One of the successes of a manufacturing company in increasing revenue is determined through the process of making the right decisions by management in obtaining efficient raw materials for production. The method that can be used by companies to assist in making decisions to buy or produce themselves is through differential analysis. The purpose of this study was to determine the difference in cost and the best alternative in the decision to buy or produce their own sausages at PT Ciomas Adisatwa Medan. This research uses a descriptive method with a qualitative approach. The research data was obtained through triangulation of data collection techniques, namely interviews, observation, and documentation. The data were then analyzed using interactive analysis techniques by Miles and Huberman. The results of the differential accounting analysis show that the alternative decision to buy sausages from other units is more efficient than the company's own sausage production decisions with production cost savings of Rp. 27,000,000/month or Rp. 324,000,000/year. Thus, the best decision for the company PT Ciomas Adisatwa Medan regarding the cost efficiency of sausage production is the decision to buy from another unit because the production costs incurred are minimal and result in reduced costs compared to producing the sausages themselves.